Cost‐effectiveness of hepatitis C virus test‐and‐treat and risk reduction strategies among men who have sex with men living with HIV in France. Issue 12 (30th November 2022) - Castry, Mathieu; Cousien, Anthony; Champenois, Karen; Supervie, Virginie; Velter, Annie; Ghosn, Jade; Yazdanpanah, Yazdan; Paltiel, A. David; Deuffic‐Burban, Sylvie
Abstract: Introduction: Studies suggest that hepatitis C virus (HCV) micro‐elimination is feasible among men who have sex with men (MSM) living with human immunodeficiency virus (HIV), through treatment‐as‐prevention and interventions aimed at reducing risk behaviours. However, their economic impact is poorly understood. The aim of this study was to assess the cost‐effectiveness of HCV screening and risk reduction strategies in France. Methods: A compartmental deterministic mathematical model was developed to describe HCV disease transmission and progression among MSM living with HIV in France. We evaluated different combinations of HCV screening frequency (every 12, 6 or 3 months) and risk reduction strategies (targeting only high‐risk or all MSM) from 2021 onwards. The model simulated the number of HCV infections, life‐expectancy (LYs), quality‐adjusted life‐expectancy (QALYs), lifetime costs and incremental cost‐effectiveness ratio (ICER) over a lifetime horizon (leading to an end of the simulation in 2065). Results: All strategies increased QALYs, compared with current practices, that is yearly HCV screening, with no risk reduction. A behavioural intervention resulting in a 20% risk reduction in the high‐risk group, together with yearly screening, was the least expensive strategy, and, therefore, cost‐saving compared to current practices. The ICER per QALY gained for the strategy combining risk reduction for the high‐risk group with 6‐month HCV screening, compared to risk reduction with yearly screening, was €61, 389. It also prevented 398 new HCV infections between 2021 and 2065, with a cost per infection averted of €37, 790. All other strategies were dominated (more expensive and less effective than some other available alternative) or not cost‐effective (ICER per QALY gained > €100, 000). Conclusions: In the French context, current HCV screening practices without risk reduction among MSM living with HIV cannot be justified on economic grounds. Risk reduction interventions targeted to high‐risk individuals—alongside screening either once or twice a year—could be cost‐effective depending on the policymaker's willingness‐to‐pay.